International evidence: Supreme Audit Institution oversight and government governance roles in achieving Sustainable Development Goal 1 - Awalia, Dzur; Abdullah, Muhammad Ikbal; Furqan, Andi Chairil; Megawati, Megawati (Badan Pemeriksa Keuangan Republik Indonesia, 2024)
Poverty reduction is both a key goal and a prerequisite for sustainable development, requiring improved oversight and governance for lasting impact. This study examines the role of Supreme Audit Institutions (SAI) oversight and effective government governance in achieving the United Nations (UN) Sustainable Development Goal (SDG) 1, which focuses on poverty alleviation. This study integrates government governance, SAI oversight, and economic indicators to offer new insights into the factors influencing SDG 1 for poverty alleviation. Using multiple linear regression on data from 116 UN member countries in 2021, this study analyzes the impact of SAI oversight and government governance quality on SDG 1. Gross domestic product (GDP) and gross national income (GNI) serve as control variables to evaluate their role in poverty reduction. The findings indicate that stronger SAI oversight and improved governance significantly contribute to poverty reduction efforts aligning with SDG 1. Economic factors, including larger GDP and country classification (developed vs. developing), also show positive effects, highlighting the role of resources and governance capacity in poverty alleviation. Strengthening SAI oversight and government governance is essential to accelerate SDG 1 achievement, with theoretical and practical policy implications. Economic resources, such as GDP and GNI, are also critical in supporting sustainable poverty reduction.